Doing drug market research critically through a lens of assumed differentiation: "Seeing’ the ‘invisible" - Coomber, Ross (Criminological connections, directions, horizons, 2025)
Recent events such as the child sexual exploitation scandals in places such as Rotherham and Rochdale (UK) have led to a new lens on vulnerability and exploitation employed in relation to those who were previously not seen to be particularly vulnerable or exploited and who, to a certain extent, were, defacto, invisible to ‘the system’. In the area of drug market research, early pathbreaking work (Dorn, Murji and South ,1992; Ruggiero and South, 1995; Ruggiero and South, 1997) permitted us to ‘see beyond’ widespread assumptions and revealed the important complexity and nuance within them that was almost invisible to the criminal justice system. My own work (particularly Coomber, 2006; Coomber and Turnbull, 2007; Coomber and South, 2004) was strongly influenced by this critical approach that looked to go behind and beyond extant assumptions. Depending on the lens adopted, research focus (or, more importantly, what it does not focus on) and research reporting will, to a greater or lesser degree, reinforce existing tropes and stereotypes. In this chapter, it is suggested that research on drug markets too often suffers from this problem and that a focus on the assumed and visible (re)produces images that impact and reinforce the validity of extant policy and practice, which often increase harms to those focused on. Whether it is ‘seeing’ and understanding ‘drug markets’, ‘addiction’, ‘drug users’ or ‘drug dealers’ one dimensionally or mainly focusing on the ‘visible’ such as violence in drug markets, the helplessness of dependency or the ‘badness’ of drug dealers, the outcome of reinforcing an imagined essence (of what is being explored) is unhelpful. This chapter will argue that too often drug field researchers (from PhD students to funded studies) do not adopt a sufficiently flexible and critical lens to enable them to see difference/differentiation or to see or understand the importance of the less visible in the fields they research. It will also outline some of the ways in which unhelpful research and writing strategies further contribute to this unhelpful perpetuation of stereotypes and over-homogenised images.